Public administration : a very short introduction - Theodoulou, Stella Z.; Roy, Ravi K., 1969- ([Oxford] : Oxford University Press, 2016)
In a modern democratic nation, everyday life is shaped by the decisions of those who manage and administer public policies. This Very Short Introduction provides a practical insight into the development and delivery of the decisions that shape how individuals, and society as a whole, live and interact.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 17, 2016).
Keywords: Public administration